Correlation between Stress/Strain and the Retention of Lipoproteins and Rupture in Atheromatous Plaque of the Human Carotid Artery: A Finite Element Study - Hiroshi YAMADA; Kazuhiro YURI; Noriyuki SAKATA (Journal of Biomechanical Science and Engineering, 2010)
We evaluated mechanical states in an atheromatous artery and correlated these values with both lipoprotein retention in a regionally thickened wall and the rupture of a luminal plaque. We used two specimens of common carotid arteries dissected at autopsy; one specimen had diffuse intimal thickening and the other had an atherosclerotic plaque. Mechanical properties were identified by cyclic inflation tests. Stress-released geometries were obtained ring specimens via a radial cut. Finite element (FE) analyses were performed on the stress-released geometry, postulating two incompressible isotropic hyperelastic models for the vascular tissues and a lipid pool. Stress/strain values and their variations were obtained under a constant axial stretch of 1.07 and intraluminal pressures ranging from 10 to 16 kPa. Light microscopy was also performed on stained specimens. Results from the FE analysis showed that the variation in maximum principal stress was ‹ 10 kPa in the deep intimal layer of a regionally thickened wall. Maximum principal stress and variation concentrated at 655 kPa and 281 kPa, respectively, at a shoulder in the plaque cap region. Maximum principal strain variation in the region of the atheromatous plaque was much lower than in the corresponding region of the artery with intimal thickening. Low stress/strain variations are likely to retain the lipid pool after formation in the thickened wall region, where the convection force seems to be very low. Both concentrations of stress and variations in stress are likely to cause a rupture at the plaque cap shoulders, which are one of the reported sites.